Double Identity - Haddix, Margaret Peterson (New York Simon & Schuster Books for Young Readers, 2005)
Thirteen-year-old Bethany's parents have always been overprotective, but when they suddenly drop out of sight with no explanation, leaving her with an aunt she never knew existed, Bethany uncovers shocking secrets that make her question everything she thought she knew about herself and her family.
810L
Ages 10-14.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
86957
Keywords: Cloning -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Secrecy -- Juvenile fiction; Aunts -- Juvenile fiction